Análisis de la jurisprudencia emitida en la última década respecto a la caducidad de la facultad determinadora de la administración tributaria - Toca Calderón, Paulina Susana (2017)
The criterion expiration SRI occurs because of term expiry probably this is not fulfilled because it is subject to arising situations that may suspend the expiration, taking into account as well as the legislation extends a determiner faculty, it also establishes. the ways in which you can suspend the deadline for the expiration handing over the administration continue through the determiner faculty of the foregoing, the Tax Code in its Article 95 sets; "The limitation periods are interrupted by the legal notice of the order of verification issued by competent authority" then it states that the order of determination loses legal effect when acts of control do not start from twenty working days in which the count starts when the order of determination is notified, or also, if already started this process will come to suspend for more than fifteen days consecutively, however, the active subject may request be granted a new order of determination, provided that the expiry date is found, according to the provisions of this Art. 95 pending.